KONSEP KAJIAN FILSAFAT ILMU DAN ILMU FILSAFAT PERSPEKTIF PENDIDIKAN ISLAM - Yudistira Nugraha, Muhammad; Rahmania, Elvina; Yolanda; Ibrahim, Duski; Syarnubi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research aims to find out how the concept of studying philosophy of science and philosophy of science from the perspective of Islamic education. The type of research used, namely library research, is a method of collecting data by seeking to understand and learn theories from various literature related to the research being studied, the source is in the form of books and websites referring to literature in line with the discussion of the research. The approach used is "content analysis" in collecting data, namely by reading and understanding supporting data in the form of articles, books, magazines, notes and websites that refer to literature that is a reference for discussion in the research. The results of the study show that the concept of Philosophy of Science is reviewed based on the perspective of Islamic education, still including the realms of anthology, epistimology and axiology which can later answer the challenges of problems in Islamic education. The realm of anthology is related to the problem of the nature of science to study the substance of human beings in Islam, while epistemology examines the education system, and axiology examines the concept of values that are reflected in the reality of life with the goal of realizing divine values and human values. While Philosophy in the perspective of Islamic education is an effort that is made tirelessly, constantly trying to find a truth, this is certainly in line with Islamic education which does not justify a desperate attitude, of course, Islamic education forms a personality that has fighting power in solving a problem.